1984
DOI: 10.7589/0090-3558-20.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Elaeophora schneideri Wehr and Dickmans, 1935 in White-tailed Deer from the Edwards Plateau of Texas

Abstract: The arterial nematode, Elaeophona

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the southeastern United States, sublingual impactions, which apparently are unique to white-tailed deer, have been reported only from areas where E. schneideri is enzootic in whitetails (Prestwood and Ridgeway, 1972;Hibler and Prestwood, 1981). Identical impactions also have been reported in white-tailed deer from Kerr County, Texas (Van Volkenberg and Taylor, 1943), and though the deer were not examined for arterial worms at the time of that study, more recent reports have indicated that the parasite is enzootic in Kerr County (Robinson et al, 1978;Waid et al, 1984). Neither of the latter workers reported food impactions in infected white-tailed deer, however.…”
Section: Discussionmentioning
confidence: 79%
“…In the southeastern United States, sublingual impactions, which apparently are unique to white-tailed deer, have been reported only from areas where E. schneideri is enzootic in whitetails (Prestwood and Ridgeway, 1972;Hibler and Prestwood, 1981). Identical impactions also have been reported in white-tailed deer from Kerr County, Texas (Van Volkenberg and Taylor, 1943), and though the deer were not examined for arterial worms at the time of that study, more recent reports have indicated that the parasite is enzootic in Kerr County (Robinson et al, 1978;Waid et al, 1984). Neither of the latter workers reported food impactions in infected white-tailed deer, however.…”
Section: Discussionmentioning
confidence: 79%
“…In these hosts, prevalence of E. schneideri is high, reaching levels of 78–100% [ 26 , 32 ]. However, the parasite has also been reported in white-tailed deer in Florida, Georgia, South Carolina and Texas with a much lower prevalence of 2–10% [ 24 , 40 ]. It is speculated that the emergence of E. schneideri in the southeastern USA is a consequence of the translocation of infected deer from endemic areas in the West [ 25 , 31 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elaeophora schneideri (Nematoda: Filariidae) was first described by Wehr and Dikmans (1935) in domestic sheep (Ovis aries) and mule deer (Odocoileus hemionus hemionus) from New Mexico, and has been reported subsequently from seven Western states: Arizona (Hibler and Adcock, 1968), California (Weinmann et al, 1973), Colorado (Madden, et al, 1991), Montana (Worley, 1975), Texas (Waid et al, 1984), Utah (Jensen et al, 1982), and Wyoming (Abdelbaki, 1975). In addition, it has also been reported from three Southeastern states: Georgia, Florida, and South Carolina (Couvillion et al, 1984) as well as from British Columbia in Canada (Cowan, 1946).…”
mentioning
confidence: 99%